1994
DOI: 10.1128/jvi.68.11.7654-7658.1994
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the fusion peptide and heptad repeat regions of the Newcastle disease virus fusion protein block fusion

Abstract: Nonconservative mutations were introduced by site-specific mutagenesis into the fusion peptide and the adjacent heptad repeat region of the fusion protein of Newcastle disease virus in order to determine the role of both regions in the fusion activity of the protein. Mutations in both regions that allowed for proper folding and intracellular transport of the protein blocked the fusion activity of the protein when assayed in the presence of the hemagglutinin-neuraminidase protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 28 publications
2
41
0
2
Order By: Relevance
“…As has been well documented for the paramyxovirus F protein and other class I viral fusion proteins, nonpolar residues at the a and d positions in the HRA region are important in the formation of the coiled-coil hairpin (18,19,31,55). Mutations to individual a and d residues in HRA also affect the folding and fusogenic activity of intact NDV and PIV5 F proteins (51,53,60), a finding that suggests that these residues are important in the formation and activation of the native conformation of the F protein. Many other HRA residues, in addition to a and d residues, are involved in structural interactions that maintain the prefusion conformation of the F protein (64).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As has been well documented for the paramyxovirus F protein and other class I viral fusion proteins, nonpolar residues at the a and d positions in the HRA region are important in the formation of the coiled-coil hairpin (18,19,31,55). Mutations to individual a and d residues in HRA also affect the folding and fusogenic activity of intact NDV and PIV5 F proteins (51,53,60), a finding that suggests that these residues are important in the formation and activation of the native conformation of the F protein. Many other HRA residues, in addition to a and d residues, are involved in structural interactions that maintain the prefusion conformation of the F protein (64).…”
Section: Discussionmentioning
confidence: 93%
“…Many of the conservative mutations to HRA residues reduce expression of the SeV F protein. Mutation of nonpolar "a" and "d" residues in HRA of the NDV F protein to lysine residues decreases cell surface expression and eliminates membrane fusion activity (51,53). In contrast, mutation of a and d residues in HRA of the PIV5 F protein to methionine residues does not, in many cases, disrupt the ␣-helix formation, protein expression and processing, or membrane fusion activity (60).…”
Section: Resultsmentioning
confidence: 99%
“…Those include sequence conservation among coronaviruses, hydrophobicity, richness in alanine and glycine residues, and the ability to be modeled into a sided helix and bounded by charged residues. Studies of heptad repeat regions in many viral fusion proteins have revealed that they are also essential for membrane fusion (Buckland et al, 1992;Dubay et al, 1992;Sergel-Germano et al, 1994). Although fusion peptides are generally found adjacent to heptad repeats but not within the heptad repeat, there is no indication that fusion peptides cannot reside in a heptad repeat.…”
Section: Discussionmentioning
confidence: 99%
“…Although fusion peptides are generally found adjacent to heptad repeats but not within the heptad repeat, there is no indication that fusion peptides cannot reside in a heptad repeat. It is postulated that heptad repeats may also be able to insert into membranes to help elicit fusion because of the amphipathic nature of their helices (Segrest et al, 1992;Sergel-Germano et al, 1994). Synthetic peptides representing part of the influenza virus HA heptad repeat region have been shown to insert reversibly into phospholipid vesicles under endosomal pH conditions (Yu et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The HN glycoprotein is involved in attachment and release of virus and the F glycoprotein mediates fusion of the viral envelope with cellular membranes [6]. Mutational analysis has shown that the fusion peptide and the adjacent heptad repeat region play a role in the fusion activity of F protein [7]. This protein is synthesized as a precursor, F 0 , which must be proteolytically cleaved to F 1 and F 2 to activate fusion [6,8].…”
Section: Introductionmentioning
confidence: 99%